Teaching and learning fraction: A systematic literature review - Chn, Rafika Riana; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Hartono, Yusuf; Susanti, Ely; Nusantara, Duano Sapta (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
Fractions are one of the materials that have an important role in mathematics learning both domestically and abroad. Therefore, several articles discussing fractions published in several journals can be found in several sources, both national and international. This article aims to provide an overview of learning fractions, especially in context, activities and learning outcomes based on relevant literature. Therefore, we are interested in conducting a Systematic Literature Review (SLR) of the 10 articles resulting from the Meta analysis (PRISMA) process. This research focuses on three aspects, namely: 1) Activities and contexts used in learning fraction material, 2) Learning outcomes related to the application of these activities and contexts and 3) Main findings in the research. Systematic literature review found that there were 10 contexts and activities implemented in learning fraction material. Apart from that, we also concluded that the holistic, interactive and contextual learning approach, namely PMRI, had a positive impact on students' understanding of fraction material. Providing meaningful and relevant experiences can increase student interest and build a strong foundation for further mathematical understanding. The results of this research can provide a summary of existing literature and literature to identify weaknesses or gaps for further investigation in future research related to the topic of fractions.